The structure type ZrAl0.23Ge1.77 - Maryskevych, D.; Tokaychuk, Ya.; Akselrud, L.; Gladyshevskii, R. (Physics and Chemistry of Solid State, 2023)
The new ternary intermetallic compound ZrAl0.23Ge1.77 was observed after annealing at 600°C, and its crystal structure was determined by X-ray single-crystal diffraction. The structure (own structure type, Pearson symbol tI32-8, space group I41/amd, a = 3.8013(2), c = 29.893(3) Å, Z = 4) is a variant with partial positional disorder of the pseudo-binary structure type Zr0.75AlSi1.25. The structures are members of the family of linear intergrowth structures composed of AlB2-type slabs (layers of centered trigonal prisms) and CaF2-type slabs (layers of empty “half octahedra”), here in the ratio 1:2. The structure of ZrAl0.23Ge1.77 is characterized by statistical occupation by Al and Ge of one of the sites forming the CaF2-type slabs and positional disorder of the Ge atoms that form zig-zag chains along the crystallographic direction [100].